Guidelines in Chemotherapy - Atmakusuma, Djumhana; Hospital, Dharmais Cancer (Indonesian Journal of Cancer, 2008)
Guidelines in ChemotherapyÂ full text: http://www.scribd.com/doc/45151303/Guidelines-in-Chemotherapy